2021
DOI: 10.3390/su13094629
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Stress in Plants: Toxicity, Tolerance and Phytoremediation

Abstract: Extensive industrial activities resulted in an increase in chromium (Cr) contamination in the environment. The toxicity of Cr severely affects plant growth and development. Cr is also recognized as a human carcinogen that enters the human body via inhalation or by consuming Cr-contaminated food products. Taking consideration of Cr enrichment in the environment and its toxic effects, US Environmental Protection Agency and Agency for Toxic Substances and Disease Registry listed Cr as a priority pollutant. In nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 131 publications
3
50
0
5
Order By: Relevance
“…The values of Cr retained in the MB tissues were quite high and varied for stems and leaves from 1100 mg/kg dw to 1700 mg/kg dw and from 2900 mg/kg dw to 5500 mg/kg dw for roots and rhizomes, respectively for pots 1-2 and for pots 3-4 without showing toxic effects that could alter physiological and metabolic pathways [65]. These values are comparable with those for other hyperaccumulator species such as Cannabis sativa and Allium griffithianum, which can accumulate higher concentrations of Cr ranging from 568.33 to 1233.3 mg/kg [66], and Diectomis fastigiata, which can accumulate Cr in roots at about 2371 mg/kg, while Vernonia cinerea can accumulate 5500 mg/kg dry weight Cr in shoots [67]. The values in milligrams of Cr per gram of biomass shown are slightly lower th the values observed in the previous experiment [11], particularly for Pots 3 and 4, du the greater development of biomass, and they should reflect higher tolerance to Moreover, it should be noted that there is a tendency of the plant to store other Cr dur subsequent growth, confirming the possibility for MB to act as a hyperaccumulator of metal.…”
Section: Cr Distribution In Tissuessupporting
confidence: 50%
“…The values of Cr retained in the MB tissues were quite high and varied for stems and leaves from 1100 mg/kg dw to 1700 mg/kg dw and from 2900 mg/kg dw to 5500 mg/kg dw for roots and rhizomes, respectively for pots 1-2 and for pots 3-4 without showing toxic effects that could alter physiological and metabolic pathways [65]. These values are comparable with those for other hyperaccumulator species such as Cannabis sativa and Allium griffithianum, which can accumulate higher concentrations of Cr ranging from 568.33 to 1233.3 mg/kg [66], and Diectomis fastigiata, which can accumulate Cr in roots at about 2371 mg/kg, while Vernonia cinerea can accumulate 5500 mg/kg dry weight Cr in shoots [67]. The values in milligrams of Cr per gram of biomass shown are slightly lower th the values observed in the previous experiment [11], particularly for Pots 3 and 4, du the greater development of biomass, and they should reflect higher tolerance to Moreover, it should be noted that there is a tendency of the plant to store other Cr dur subsequent growth, confirming the possibility for MB to act as a hyperaccumulator of metal.…”
Section: Cr Distribution In Tissuessupporting
confidence: 50%
“…In Chile, there is no legislation relative to pollutants in soils; for that reason, the Dutch Environmental Standard was used for comparison [ 48 ], and according to this, the intervention values for Zn and Ni are 720 and 100 mg kg −1 dry weight. They are not indicated for Cr [ 48 ], but Srivastava et al [ 16 ] indicated an acceptable level in soils for human health and the environment of 64 mg kg −1 . The lack of regulations produced a high number of abandoned tailings in Northern and Central Chile.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of abandoned mine tailing impoundments, negative environmental impacts have been identified, including an increase in the concentration of metals in agricultural soils, sediments, animals, human beings, and plants [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Among the various heavy metals, chromium (Cr) is widely present in soils, with an average concentration of 60 mg kg −1 [ 16 ]. Chromium is a nonessential element for plants, and it produces toxic effects in most of them at 5 mg kg −1 , with a normal concentration in plants being less than 1 mg kg −1 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A promising remediation strategy is the use of living organisms including fungi, algae, bacteria, and plants ( Fernández et al, 2018 ; Chen and Tian, 2021 ). In order to plan effective phytoremediation strategies and understand Cr detoxification processes, it is necessary to know about the uptake and metabolism of Cr in plants ( Bluskov et al, 2005 ; Shahid et al, 2017 ; Vidayanti et al, 2017 ; Srivastava et al, 2021 ). In such studies, Cr speciation and bio-imaging play a crucial role.…”
Section: Introductionmentioning
confidence: 99%